Polymer science and technology for scientists and engineers - Pethrick, R. A. 1942- (Whittles, 2010)
"This introductory text in the field of plastics provides the engineer, who is likely to be using plastics, with sufficient understanding of the properties of polymers and composites so that they can effectively design components that will be used in industry. The book also includes chapters on composites, case studies, and environmental issues. Finally, this resource provides a simple method of polymer identification that the engineer can use as a first analysis of a material."-- Publisher's description